2019
DOI: 10.4317/medoral.23020
|View full text |Cite
|
Sign up to set email alerts
|

Validation of microRNA expression profile in Oral Lichenoid Disease through cytological samples

Abstract: BackgroundTo validate oral exfoliative cytology in the analysis of the microRNA expression profile in Oral Lichenoid Disease (OLD).Material and MethodsThe expression of 13 microRNAs identified and presented by our group in a previous study was analyzed in 26 cases, 16 diagnosed as OLD and 10 controls with no oral mucosal pathology. Cytological samples from the oral mucosa obtained using an Orcellex toothbrush were analyzed using RT-qPCR and TaqMan microRNA assays.ResultsThe aberrant expression was validated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In lichen planus, cytological examination usually reveals a large number of lymphocytes in the affected area, many activated macrophages, and plasma cells are less common [25].…”
Section: Results Of the Study And Discussionmentioning
confidence: 99%
“…In lichen planus, cytological examination usually reveals a large number of lymphocytes in the affected area, many activated macrophages, and plasma cells are less common [25].…”
Section: Results Of the Study And Discussionmentioning
confidence: 99%
“…In addition, it reduces the problem related to sampling in the preparation of smears, it reduces false negative rates; and therefore, it improves the sensitivity and quality of the cytology 6,7 . However, the lack of studies reporting oral LBC‐standardized protocols, and the elevated cost of materials and methodologies, challenges its adoption in the daily clinical practice and research 5,8‐13 . There is a need of having a low cost, reproducible, and easily accessible protocol; available worldwide that could be implemented for the cellular and molecular study of several oral mucosa lesions, so that cytopathologists could have an additional and complementary diagnostic tool, with a considerable potential for their early detection.…”
Section: Introductionmentioning
confidence: 99%
“…According to the search strategy described in Table S1, a total of 9 eligible studies on 19 aberrant miRNAs are identified (Cheng et al, 2021;Gissi et al, 2018;He et al, 2016;Lin et al, 2022;Setién-Olarra et al, 2019;Tu et al, 2022;Yap et al, 2018;Yap et al, 2019;Zhou et al, 2017). There are 243 OSCC patients, 116 OPMD patients, and 307 normal controls.…”
mentioning
confidence: 99%